SURVEI MINAT BELAJAR PADA MATA PELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (PJOK) PADA MASA PANDEMI DI SMP NEGERI 44 SURABAYA - Sutrisno (LPPM STKIP PGRI Sidoarjo, 2021)
The presence of the Covid-19 pandemic has an impact on the world of education, especially in Indonesia, which requires all activities to be carried out from home, including teaching and learning activities. Teaching and learning activities during the pandemic are carried out online. However, in the implementation process, online learning may not run optimally and affect student learning motivation. The purpose of this study was to determine the motivation of class 7F students in the subjects of Physical Education, Sports and Health (PJOK) at SMP Negeri 44 Surabaya in 2020/2021. To find out students’ interest in learning in learning activities during the Covid-19 pandemic, this research is a descriptive quantitative study with the type of survey research. The population in this study was the 7th grade students of SMP Negeri 44 Surabaya in the academic year 2020/2021, totaling 360 students. The sample in this study used total random sampling, namely quota sampling with class 7F from the total population, so the sample size in this study was 40 students. The data were analyzed using quantitative descriptive statistics with the category of interval data. The result of this research was that from 40 students, as many as 25 students were in the very high category, 10 students were in the high category, 5 students were in the medium category, and 0 was in the low category. The results of the research of students who took part in learning during the Covid-19 pandemic scored an average of 70 on a high score scale. Thus, it can be concluded that students’ motivation to participate in learning activities during the Covid-19 pandemic is relatively high. This study provides practical implications as a benchmark for teacher performance in learning activities during the Covid-19 pandemic